A Concise History of Canada / [electronic resource] - Conrad, Margaret (Cambridge : Cambridge University Press, 2012)
Margaret Conrad's history of Canada begins with a challenge to its readers. What is Canada? What makes up this diverse, complex and often contested nation-state? What was its founding moment? And who are its people? Drawing on her many years of experience as a scholar, writer and teacher of Canadian history, Conrad offers astute answers to these difficult questions. Beginning in Canada's deep past with the arrival of its Aboriginal peoples, she traces its history through the conquest by Europeans, the American Revolutionary War and the industrialization of the nineteenth and twentieth centuries to its prosperous present. Despite its successes and its popularity as a destination for immigrants from across the world, Canada remains a curiously reluctant player on the international stage. This intelligent, concise and lucid book explains just why that is.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).